Youth attitudes towards empowerment programs and public participation in Abu Dhabi - Al-Hammadi, Fatma Abdulla; Al-Gharaibeh, Fakir M. (Al-Adab Journal, 2021)
This study aimed to identify youth attitudes towards empowerment programs and public participation in Abu Dhabi, by identifying empowerment programs directed for youth, and their attitudes towards registration process in these programs, and the role of these programs in developing their skills and abilities all from their point of view. And their participation in public life. This study used the descriptive survey approach (a quantitative study), and the intended sample consisted of (373) youth in the age group (19-35) years (males / females) who were benefiting from empowerment programs in Abu Dhabi. The data collection tool was the questionnaire, and the most important conclusions of the study were that there is a clear interest on the part of government agencies to design and implement programs to empower youth and develop their skills and abilities. The programs are in line with the needs and goals of young people, and contribute to strengthening many positive values ​​for them, the most important of which is the spirit of positive citizenship and the concept of tolerance, enhancing their sense of social responsibility, developing their skills in teamwork in addition to developing youth skills in investing their time effectively.